The role of collective action and property rights in climate change strategies - CGIAR Program on Collective Action and Property Rights (International Food Policy Research Institute, 2010)
The well-documented threats posed by climate change are serious and potentially devastating to the global community. The geographic areas that are most susceptible to the effects of climate change episodes such as increased droughts and flooding are also the regions where the majority of the world's poor live. Evidence suggests that these effects may be especially severe for Importance of Institutions in Addressing Climate Change disadvantaged communities in developing countries. The poor have few assets and few income diversification opportunities, which severely limit their ability to cope or adapt to climate changes.